2014
DOI: 10.2147/ndt.s67805
|View full text |Cite
|
Sign up to set email alerts
|

Altered intrinsic regional brain activity in male patients with severe obstructive sleep apnea: a resting-state functional magnetic resonance imaging study

Abstract: BackgroundPrevious studies have demonstrated that obstructive sleep apnea (OSA) is associated with abnormal brain structural deficits. However, little is known about the changes in local synchronization of spontaneous activity in patients with OSA. The primary aim of the present study was to investigate spontaneous brain activity in patients with OSA compared with good sleepers (GSs) using regional homogeneity (ReHo) analysis based on resting-state functional magnetic resonance imaging (MRI).MethodsTwenty-five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 45 publications
3
51
1
Order By: Relevance
“…The current findings dovetail with a growing literature suggesting that sleep and DMN connectivity are closely linked. Specifically, this study suggests that in addition to sleep deprivation 4,6 , quality 36 , and disorders, such as insomnia and OSA 3,5,20 , greater sleep/wake irregularity may impact network structure within the DMN. Previously, reduced DMN functional connectivity has been proposed as a neural substrate of the behavioral correlates for sleep deprivation 4 and/or may reflect a "local sleep" in which a portion of the brain enters a sleep state when an individual is otherwise conscious 7,55 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The current findings dovetail with a growing literature suggesting that sleep and DMN connectivity are closely linked. Specifically, this study suggests that in addition to sleep deprivation 4,6 , quality 36 , and disorders, such as insomnia and OSA 3,5,20 , greater sleep/wake irregularity may impact network structure within the DMN. Previously, reduced DMN functional connectivity has been proposed as a neural substrate of the behavioral correlates for sleep deprivation 4 and/or may reflect a "local sleep" in which a portion of the brain enters a sleep state when an individual is otherwise conscious 7,55 .…”
Section: Discussionmentioning
confidence: 90%
“…Specifically, prior work has shown that sleep deprivation results in reduced functional connectivity of the DMN and the DMN-ACN anticorrelation during both rest and task performance and among both young and older adults 4,6 . In addition, reduced DMN connectivity has been observed among young and elderly adults who report high levels of daytime sleepiness 7 as well as individuals diagnosed with insomnia and obstructive sleep apnea (OSA) disorders 3,5,20 . Taken together, these studies suggest a close association between sleep and DMN connectivity and highlight a potential neural mechanism by which poor sleep results in cognitive deficits.…”
mentioning
confidence: 99%
“…Previous brain Rs-MRI studies in OSA patients have revealed alterations in cerebellar, frontal, parietal, temporal, thalamic, middle and dorsal prefrontal cortex, left precentral gyrus, and posterior cingulate cortex regions 1113,16. OSA patients have abnormal Rs-FC in various brain regions that are related to affective, autonomic, sensorimotor, executive, and cognitive regulatory functions 11.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ReHo has been successfully used to explore functional modulations and to characterize pathophysiological changes in patients with sleep problems, such as obstructive sleep apnea 25 and sleep deprivation, 24 and various neuropsychiatric disorders related to mood/emotional changes, such as unhappy individuals, 26 social anxiety disorders, 27 panic disorder, 28 early life stress 29 and depression. 30 However, it has not yet been used to explore pathophysiological changes in PCPIs.…”
Section: Introductionmentioning
confidence: 99%